2020
DOI: 10.1194/jlr.ra120000951
|View full text |Cite
|
Sign up to set email alerts
|

A novel phosphoglycerol serine-glycine lipodipeptide of Porphyromonas gingivalis is a TLR2 ligand

Abstract: Porphyromonas gingivalis is a Gram-negative anaerobic periodontal microorganism strongly associated with tissue destructive processes in human periodontitis.  Following oral infection with P. gingivalis, the periodontal bone loss in mice is reported to require engagement of Toll-like receptor 2 (TLR2).   Serine-glycine lipodipeptide or glycine aminolipid classes of P. gingivalis engage human and mouse TLR2 but a novel lipid class reported here is considerably more potent in engaging TLR2 and the heterodimer re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 33 publications
2
65
0
Order By: Relevance
“…Lipid 1256 isolated from P. gingivalis was recently reported to significantly promote monocyte release of TNF-α and IL-1β from freshly isolated human peripheral blood monocytes [4]. This lipid was also shown to engage human TLR2/TLR6 in transfected human embryonic kidney cells [4]. Bone loss in experimental animals orally gavaged with P. gingivalis is reported to be mediated through engagement of TLR2 [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lipid 1256 isolated from P. gingivalis was recently reported to significantly promote monocyte release of TNF-α and IL-1β from freshly isolated human peripheral blood monocytes [4]. This lipid was also shown to engage human TLR2/TLR6 in transfected human embryonic kidney cells [4]. Bone loss in experimental animals orally gavaged with P. gingivalis is reported to be mediated through engagement of TLR2 [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The samples were centrifuged and transferred to autosampler tubes. Analysis of lipids utilized mass spectrometric instrumentation located in the Center for Environmental Sciences and Engineering at the University of Connecticut, Storrs as previously described [4]. Routine analysis of lipid samples used a Waters Acquity TM UPLC R coupled with an Acquity TM TQD TM tandem mass spectrometer (Waters Co., Milford, MA).…”
Section: Lc-ms Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Their findings also suggested that TLR2 has a microbial stimulation effect and that the activation of macrophages plays a nonnegligible role in this process. Recent cytological studies ( 49 , 50 ) have shown that P.g. is dependent on TLR2 and TLR4 for promoting the secretion of TNF-α in macrophages and is primarily stimulated by glycine lipids, such as serine-glycine dipeptide lipids, of the monomonas factor.…”
Section: Polarization Of Macrophages In Periodontitis and Its Role In Periodontitis Pathophysiologymentioning
confidence: 99%